Efecto letal de 04 Concentraciones de Baculovirus sobre larvas de Spodoptera Frugiperda (J. E. Smith) en Maíz amarillo duro variedad M-28T en Juan Guerra. - Rivero Herrera, Mario Enrique (2000)
In order to find the suitable concentration for the control of Spodoptera Frugiperda (J.E. Smíth) the most important com platge, the present in investigation work was realice, between may and august of 1 998, in the district of Juan Guerra, in San Martin region, it's located to 06° 35' south latitude and 76º 19' west longitude to 230 m.s.n.m. The installation of the experiment was realice in the zone of the Nacional Programe for the corn investigations in the E.E.”Et Porvenir" INIA. The experimental design - used, was make with blocks complitly to hazard form, with four repetitions and five treatments. In the in investigations, were study four concentrations (T1 = 25 g/ha. de VPN), T2 = 50 g/ha. de VPN. T3 = 75 g./ha. de VPN y T4.= 100 g/ha de VPN), and a witness (T5 = water), added twenty treatments in study was apply Baculovirus (Virons of poliedrose nuclear) in order to control the Spodoptera frugiperda and have plants in good conditions and quality. The fertilization was realice apply 50% of nitrogeno, and at th phosplhorus and potassium, to 15 days after of the sowing and the rest of the nitrogen to 30 days alter of the sowíng. The best and commendable resoult for the integrate cibtrik origrane was tge treatnebt T4 (100 g/ha. de VPN) with a 54,5% of mortality in the control of the Spoaoptero fruiperde.